Optical coherence tomography angiography characterisation of Best disease and associated choroidal neovascularisation. Issue 4 (1st August 2017) - Guduru, Abhilash; Gupta, Arushi; Tyagi, Mudit; Jalali, Subhadra; Chhablani, Jay
Abstract : Aims: To characterise the vasculature of the retina in patients with Best vitelliform dystrophy, including those with choroidal neovascularisation (CNV), using optical coherence tomography angiography (OCTA) and correlate with fluorescein angiography (FA). Methods: This prospective observational study included 19 eyes of 10 patients with Best disease. Using OCTA, all layers of retina were qualitatively characterised for each eye. Patients with CNV also underwent FA, and areas of CNV were measured by OCTA and FA and correlated. Results: Retinal characteristics revealed 14 (74%) eyes with abnormal foveal avascular zone (FAZ) in the superficial layer, 19 eyes (100%) had an abnormal FAZ in deep layers, 11 (58%) eyes had a hyper-reflective centre in the superficial layer, 18 (95%) had patchy vascularity loss in the deep layer, 17 (89%) eyes had hyporeflective centre in the choriocapillary (CC) layer and 12 (63%) of those eyes had hyper-reflective material within the hyporeflective centre. Also, notably 6 (86%) CNV eyes had a "halo" or a hypolucent area surrounded in the CNV complex in the outer retinal layer. CNV patterns resembled dense net, loose net, mixed and a new found pattern of a ring shape. CNV measurements revealed an average area of 1.66±1.18mm 2 using OCTA and an average area of 0.88±0.76mm 2 1 using FA (p=0.15). Conclusion: OCTA reveals that eyes with Best disease have abnormal FAZ, patchy vascularity loss in the superficial and deep layers of the retina and capillary dropout with a hyporeflective centre in CC layer. Further, OCTA is superior to FA in measuring CNV.